U.S. Neurosurgical Response to COVID-19: Forging a Path Toward Disaster Preparedness. Issue 5 (3rd May 2021) - Ravindra, Vijay M; Dunn, Gavin P; Belverud, Shawn; Carroll, Christopher P; Zuckerman, Scott L; Menger, Richard; Malone, David; Cooke, Jonathon; Porenksy, Paul; Klugh III, Arnett; Gilhooly, Jonathan; Tomlin, Jeffrey; et al.
ABSTRACT: Introduction: The worldwide COVID-19 pandemic poses challenges to healthcare capacity and infrastructure. The authors discuss the structure and efficacy of the U.S. Navy's response to COVID-19 and evaluate the utility of this endeavor, with the objective of providing future recommendations for managing worldwide healthcare and medical operational demands from the perspective of Navy Neurosurgery. Materials and Methods: The authors present an extensive review of topics and objectively highlight the efforts of U.S. Navy Neurosurgery as it pertains to the humanitarian mission during the COVID-19 pandemic. Results: During the humanitarian mission (March 27, 2020–April 14, 2020), the response of active duty and reserve neurosurgeons in the U.S. Navy was robust. Neurosurgical coverage was present on board the U.S. Navy Ships Mercy and Comfort, with additional neurosurgical deployment to New York City for intensive care unit management and coverage. Conclusions: The U.S. Navy neurosurgical response to the COVID-19 pandemic was swift and altruistic. Although neurosurgical pathologies were limited among the presenting patients, readiness and manpower continue to be strong influences within the Armed Forces. The COVID-19 response demonstrates that neurosurgical assets can be rapidly mobilized and deployed in support of wartime, domestic, and global humanitarian crises to augment both trauma and critical care capabilities.